Gender, Authority, and Islamic Legal Administration: Rethinking Women’s Eligibility as Penghulu in Indonesia - Jamiliya Susantin; Yusron Palevi; Wahyuni Danial Khotimah; Ahmad Izzuddin (At-Tafkir, 2025)
The position of penghulu holds a strategic role in the administration of Islamic family law in Indonesia. Although existing state regulations do not explicitly restrict this position based on gender, women’s participation as penghulu remains limited, indicating a gap between legal norms and institutional practice. This research aims to examine the position of female penghulu by clarifying the conceptual distinction between penghulu as an administrative state office and wali hakim as a judicial-religious authority, a distinction that is often blurred in policy implementation and public perception. This study employs a qualitative literature-based approach using normative-critical analysis grounded in legal feminism. The analysis is supported by Buya Husein Muhammad’s gender-responsive Islamic thought and Prof. Hasbi As-Shiddiqi’s concept of Indonesian fiqh, which emphasizes contextual and sociological considerations in Islamic legal interpretation. The findings reveal that obstacles to women’s participation as penghulu do not stem from Islamic legal prohibitions, but rather from public policy designs that conflate administrative and judicial functions, as well as from entrenched patriarchal social constructions. From a fiqh perspective, penghulu is not a pillar (rukun) of marriage, and therefore there is no normative basis requiring the position to be held exclusively by men. Furthermore, female penghulu contribute significantly to premarital education and the protection of women’s rights within marriage. This study concludes that gender-responsive reform in penghulu policy is essential to promoting inclusive, just, and contextually grounded Islamic family law services in Indonesia. Such reform has important implications for strengthening legal certainty, enhancing gender equality, and improving the quality of public religious services within the framework of national Islamic law administration.